PHYSICS LEARNING BLOG DEVELOPMENT BASED ON FLIPPED CLASSROOM APPROACH FOR GRADE X MIPA SENIOR HIGH SCHOOL - Willyam Santos Alfrado; M. Rahmad; Muhammad Syafi’i; Nurliana Nurliana (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2018)
This study aims to develope physics learning blog based on flipped classroom approach for grade X MIPA Senior High School. The developed product was learning blog which can be utilized as learning media for teacher and student at flipped classroom learning. Research method used was R&D with the ADDIE design approach. Research phase includes analysis, design, development, and evaluation. Data collection instrument include a sheet of students interest in learning using of internet that filled by students and learning blog validity sheet that filled by validator. Data was analyzed using percentage methods and descriptive techniques. Learning blog which has been developed then validated by 3 physics education lecturers as experts and 3 physics teachers as users. Learning blog contain of LKPD, learning videos, online quizzes, and chat. As for the assessment includes content aspect, linguistic aspects, and display aspect. While the avarage score of learning blog validity was 3,17 from experts with high category, while those of users was 3,17 with very high category. Therefore physics learning blog based on flipped classroom approach was valid and feasible to use.